Performance Improvement of Sri Yantra Shaped Multiband Antenna with Defected Ground Structure - Krishna Kanth Varma, P; Murali Krishna, Ch; Santhi Ratna Priyanka, G (International Journal of Engineering and Technology, 2018)
A hybrid fractal antenna inspired from sri yantra geometry covering multiple bands in the microwave frequency spectrum is presented in this paper with a reduced size of 45mm x 30mm x 1.6mm. The presented design aims at a multiband antenna with a polygon slots in- scribed in a circular patch with defected ground structure and the effect of Sri Yantra fractal iterations on the antenna characteristics are also studied. The gains achieved at respective bands for Sri Yantra geometry are 4.61dB at 4.04GHz, 2.71dB at 4.94GHz, 4.77dB at 5.88GHz, 3.41dB at 6.60GHz, 5.12dB at 7.24GHz, 3.11dB at 8.88GHz and 3.47dB at 10.92GHz.Â Â